The Role of Satisfaction in Mediating the Influence of Perceived Usefulness and Perceived Ease of Use on the Intention to Reuse Ovo E-Wallet in Badung Regency - Wandarman Lombu; I Made Wardana (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The increasing number of businesses using e-commerce in Bali, the use of e-wallets like OVO is expected to integrate technology into daily life and drive the growth of the digital economy in the region. Factors indicated to influence the intention to reuse include satisfaction, perceived usefulness, and perceived ease of use. This study employs an associative research design with causal relationships and was conducted in Badung Regency. The sample size consisted of 105 respondents. Data was collected through questionnaires and then analyzed using descriptive analysis and structural equation modeling (SEM) based on PLS. The results showed that perceived usefulness has a positive and significant influence on the intention to reuse. Perceived ease of use also has a positive and significant impact on the intention to reuse. Perceived usefulness has a positive and significant effect on satisfaction. Perceived ease of use has a positive and significant effect on satisfaction. Satisfaction has a positive and significant influence on the intention to reuse. Satisfaction significantly mediates the indirect effect of perceived ease of use on the intention to reuse. It also significantly mediates the relationship between perceived usefulness and the intention to reuse. These findings underscore the importance of usefulness, ease of use, and satisfaction in increasing users' intention to continue using the technology. OVO e-wallet managers should focus on enhancing the benefits, ease of use, and user experience to improve user retention and loyalty.